Trends in cleft palate incidence in the era of obstetric sonography and early detection. (12th December 2022) - Emodi, Omri; Capucha, Tal; Shilo, Dekel; Ohayon, Chaim; Ginini, Jiriys George; Ginsberg, Yuval; Aizenbud, Dror; Rachmiel, Adi
Abstract: Background: The effect of improvement in prenatal identification of cleft lip or palate (CL/P) on termination of pregnancy (TOP) worldwide is scarcely reported. Our aim was to assess changes in the prevalence of cleft palate attributed to the high access and availability of prenatal advanced screening and pregnancy termination in Israel. Methods: A retrospective study was conducted on CL/P patients which were treated in our institute and born between January 2000 and December 2018. Clinical and demographic data were extracted from medical records. Data on TOP were collected based on accessible information from the Ministry of Health. Cleft palate severity was evaluated using the Veau Classification. Results: The study was conducted on 258 patients. Higher incidence of Veau II and III was evident throughout the examined period (2000–2018). However, when evaluating the incidence per year, we found that the incidence of severe cases (Veau III and IV) decreased every year showing a major decline of 60% in the last decade, whereas mild cases (Veau type I and II) demonstrated a marked increase of 90%. Regarding the incidence of abortions in Israel, a decrease of 30% was observed in the last two decades, meanwhile a substantial increase was detected in the rate of abortions related to physical malformations of the fetus. Additionally, the number of late terminations due to physical malformations significantly increased in the last decade. Conclusions: Significant decrease was observed in the incidence of severe cleft palate cases in the last decade. Concurrently, we found a substantial increase in percentage of abortions performed due to physical malformations. We suggest that these changes might be attributed to the accessibility of advanced prenatal screening and pregnancy termination in Israel under the social healthcare system.